ECONOMIC REINTEGRATION OF THE LIBERATED TERRITORIES AND STRATEGIC DEVELOPMENT DIRECTIONS OF THE NON-OIL SECTOR (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article examines the development potential of Azerbaijan’s non-oil sector in the liberated territories, with a focus on economic diversification. Using comparative, systematic, and statistical methods, it assesses agriculture, tourism, energy, logistics, and industry. Infrastructure projects, green energy zones, transport development, IDP return, and employment growth contribute to sustainable regional economic development.
Keywords: liberated territories; non-oil sector; Karabakh; Eastern Zangezur; economic development; agriculture; tourism; logistics; green energy